Measurement of the inelastic proton-proton cross section at √s = 13 TeV with the ATLAS detector at the LHC - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (Physical review letters, 2016)
This Letter presents a measurement of the inelastic proton-proton cross section using 60  μb−1 of pp collisions at a center-of-mass energy √s of 13 TeV with the ATLAS detector at the LHC. Inelastic interactions are selected using rings of plastic scintillators in the forward region (2.07<|η|<3.86) of the detector. A cross section of 68.1±1.4  mb is measured in the fiducial region ξ=M2X/s>10−6, where MX is the larger invariant mass of the two hadronic systems separated by the largest rapidity gap in the event. In this ξ range the scintillators are highly efficient. For diffractive events this corresponds to cases where at least one proton dissociates to a system with MX>13  GeV. The measured cross section is compared with a range of theoretical predictions. When extrapolated to the full phase space, a cross section of 78.1±2.9  mb is measured, consistent with the inelastic cross section increasing with center-of-mass energy.